Neurological effects of long‐term diet on obese and overweight individuals: An electroencephalogram and event‐related potential study. (24th May 2021) - Ammar Ali, Muhammad; Özöğür‐Akyüz, Süreyya; Duru, Adil Deniz; Caliskan, Melisa; Demir, Ceylan; Bostancı, Tuğba; Elsallak, Farouk; Shkokani, Mohammad; Dokur, Zümray; Ölmez, Tamer; Ergün, Can; Bebek, Nerses; et al.
Abstract: The rise of overweight and obesity across all age groups can be considered as an epidemic. A high body mass index not only has effects on longevity and quality of life of people who suffer from it but also has cognitive and neurological consequences. Executive function (EF)—or the neural regions that support it might act as causes of obesity. The aim of this study is to compare the differences between healthy and obese/overweight individuals and to understand how a prolonged diet of 2 months can affect EF event‐related potential (ERP) components. Among the ERP metrics, N1, N2, and P3 are measured. Subjects underwent a diet program and their electroencephalogram was recorded every 4–6 weeks using a Stroop paradigm experiment. As the diet progressed, it was observed that perhaps more neural networks and executive control are engaged as the diet begins to take effect. Attention to nonfood increases and more control is exhibited when participants are presented with food images and food word stimuli. Increase in the N2 and P3 components highlight how the diet affects the brain during various stages of diet plans.